1995
DOI: 10.1557/jmr.1995.1508
|View full text |Cite
|
Sign up to set email alerts
|

Pt/Ti/SiO2/Si substrates

Abstract: Pt/Ti/SiO2/Si structures have been studied to investigate the structural, chemical, and microstructural changes that occur during annealing. Grain growth of the as-deposited Pt columns was observed after annealing at 650 °C, and extensive changes in the Pt microstructure were apparent following a 750 °C anneal for 20 min. In addition, two types of defects were identified on the surfaces of annealed substrates. Defect formation was retarded when the surface was covered with a ferroelectric film. Concurrent with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
1
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 14 publications
6
40
1
1
Order By: Relevance
“…The remaining thickness of TiO x under Pt is very thin (<10 nm), compared to 20 to 25 nm expected for complete oxidation of the Ti layer. The major part of the adhesion layer has hence out-diffused into the Pt grain boundaries or the PbTiO3, in agreement with previously reported results [6,8,[10][11][12]. Most probably, the remaining TiO 2 adhesion layer is porous, as is reported for the oxidation of bulk titanium [18].…”
Section: Ti-ptsupporting
confidence: 91%
See 1 more Smart Citation
“…The remaining thickness of TiO x under Pt is very thin (<10 nm), compared to 20 to 25 nm expected for complete oxidation of the Ti layer. The major part of the adhesion layer has hence out-diffused into the Pt grain boundaries or the PbTiO3, in agreement with previously reported results [6,8,[10][11][12]. Most probably, the remaining TiO 2 adhesion layer is porous, as is reported for the oxidation of bulk titanium [18].…”
Section: Ti-ptsupporting
confidence: 91%
“…Problems with diffusion and oxidation of Ti above and below Pt occur [6,[9][10][11][12]. TiO 2 -Pt metallisations have shown far superior stability [10].…”
Section: Introductionmentioning
confidence: 99%
“…3) showed that the density of threading dislocations (labeled "O" and "A" in Fig. 3) was in the order of 5¥10 SIMS showed that the Pt electrodes on the Ti adhesion layers contained Ti, consistent with findings by others [18][19][20]. The influence of Ti underneath (111) textured Pt electrodes on perovskite film texture is well documented [21,22].…”
Section: A Srtio 3 Thin Film Microstructuresupporting
confidence: 81%
“…Although it is well-known that Ti diffuses through Pt electrodes [18][19][20][21], the precise mechanisms by which Ti underlayers control perovskite thin film textures are not fully understood. In the literature, it has been suggested that either a Pt-Ti intermetallic or TiO 2 on the Pt surface provide a templating layer for (111) epitaxial perovskite growth [14,17].…”
mentioning
confidence: 99%